Climate proofing water and sanitation services and applying integrated water resource management in slums - Heath, Thomas (Cranfield University, 2011)
This thesis assesses how climate change impacts water resources and communities and reviews how the resource can be managed in an integrated manner for small water and sanitation providers. This thesis was based upon a 10 month Knowledge Transfer Partnership (KTP) between Cranfield University and Water and Sanitation for the Urban Poor (WSUP). The aim of the project was to assess the opportunities and vulnerabilities presented by climate change and how Integrated Water Resource Management (IWRM) is relevant to water and sanitation services for the urban poor. This thesis is based on two papers prepared following the KTP. The research was based upon a literature review and field work to WSUP projects in Lusaka (Zambia), Naivasha (Kenya) and Antananarivo (Madagascar). During the field work 11 focus groups and 97 stakeholder interviews were completed, in addition direct observation was undertaken throughout. To assess the impact of climate change a vulnerability assessment methodology was developed consisting of a vulnerability assessment, reviewing climate predictions, preparing hydrology scenairios and identify adaptations. In the three cities assessed, eleven communities were visited of which eight were vulnerable to flooding and four to water shortages. The research indicated that for water and sanitation providers climate change will tend to exacerbate or relieve existing vulnerabilities rather than create new issues and to adapt, water and sanitation providers need to increase the robustness of their systems by assessing the impacts across multiple scenarios. To assess the relevance of IWRM a literature review was undertaken and a benchmarking process developed based around the main principles of IWRM and fieldwork in Zambia. The IWRM assessment found that IWRM is generally irrelevant to water and sanitation suppliers to the urban poor.